Artificial Intelligence Technologies in Education - Artamonova, Neonila; Kapinos, M. M. (ISMA University of Applied Science, 2021)
The relevance and timeliness of the development of strategies for the use of artificial intelligence (AI) in educational policy is due to global digitalization, which has intensified the transformation of all spheres of human activity, including higher education. In assessing the current state and trends in the development of advanced areas of research, analytical studies using science-metric methods play an important role. Analysis of the landscape of AI technologies has been carried out and issues of theoretical and practical use of them are discussed.
Keywords: artificial intelligence; scientometrics; strategies; educational policy